Long-acting recombinant fusion protein linking coagulation factor IX with albumin (rIX-FP) in children - Kenet, Gili; Chambost, Hervé; Male, Christoph; Lambert, Thierry; Halimeh, Susan; Chernova, Tatiana; Mancuso, Maria Elisa; Curtin, Julie; Voigt, Christine; Li, Yanyan; Jacobs, Iris; Santagostino, Elena; the PROLONG-9FP Investigator Study Group (Thrombosis and Haemostasis, 2016)
A global phase 3 study evaluated the pharmacokinetics, efficacy and safety of a recombinant fusion protein linking coagulation factor IX with albumin (rIX-FP) in 27 previously treated male children (1–11 years) with severe and moderately severe haemophilia B (factor IX [FIX] activity ≤2 IU/dl). All patients received routine prophylaxis once every seven days for up to 77 weeks, and treated any bleeding episodes on-demand. The mean terminal half-life of rIX-FP was 91.4 hours (h), 4.3-fold longer than previous FIX treatment and clearance was 1.11 ml/h/kg, 6.4-fold slower than previous FIX treatment. The median (Q1, Q3) annualised spontaneous bleeding rate was 0.00 (0.00, 0.91) and was similar between the <6 years and ≥6 years age groups, with a weekly median prophylactic dose of 46 IU/kg. In addition, patients maintained a median trough level of 13.4 IU/dl FIX activity on weekly prophylaxis. Overall, 97.2 % of bleeding episodes were successfully treated with one or two injections of rIX-FP (95 % CI: 92 % to 99 %), 88.7 % with one injection, and 96 % of the treatments were rated effective (excellent or good) by the Investigator. No patient developed FIX inhibitors and no safety concerns were identified. These results indicate that rIX-FP is safe and effective for preventing and treating bleeding episodes in children with haemophilia B with weekly prophylaxis. Routine prophylaxis with rIX-FP at treatment intervals of up to 14 days are currently being investigated in children with severe and moderately severe haemophilia B. Clinicaltrials.gov (NCT01662531)
Keywords: Haemophilia B; factor IX; on-demand treatment; prophylactic regimen; rIX-FP